2004
DOI: 10.1002/pon.795
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement outcomes for parents who lose a child to cancer: Are place of death and sex of parent associated with differences in psychological functioning?

Abstract: Despite increasing cure rates, cancer is a leading cause of non-accidental death in childhood. Models of psychosocial care in pediatric cancer may therefore need to address bereavement planning for a 'minority group' of parents (approximately 25%) for whom cure of their child is not possible. This study addresses a gap in knowledge concerning long-term bereavement and psychological outcomes for parents, as a function of the sex of the parent and the place of the child's death: home versus hospital. Fifty Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 42 publications
0
75
0
6
Order By: Relevance
“…Younger age of fathers and less time from diagnosis were linked to higher ambiguity and high emotionality. Goodenough, Drew, Higgens, and Trethewie (2004) also described higher psychological distress in fathers of younger children.…”
Section: Emotional Stressmentioning
confidence: 85%
“…Younger age of fathers and less time from diagnosis were linked to higher ambiguity and high emotionality. Goodenough, Drew, Higgens, and Trethewie (2004) also described higher psychological distress in fathers of younger children.…”
Section: Emotional Stressmentioning
confidence: 85%
“…[6][7][8] However, researchers have identified that a subset of parents continue to experience severe and escalating psychological and physical problems. [9][10][11][12] Preliminary data suggest that these parents may be experiencing symptoms that constitute prolonged grief disorder (PGD). PGD, also known as complicated grief, is defined as a persistent elevated level of grief for more than 6 months after the loss of a loved one, beyond that which is considered adaptive, due to problematic adjustment to the loss.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,15 Parental decision making about end-of-life care is associated not only with the QOL of the child, but also with the grief and depression that parents go through after the child's death. [16][17][18] It is important for health care professionals to support parents, help them come to terms with their child's condition, and aid in making end-of-life decisions; this is important so that parents can still have a sense of parenthood after the child's death. We conducted research to clarify parents' thoughts and perceptions regarding their child's diagnosis with incurable cancer and to understand the changes that occur during the end-of-life decision-making process.…”
Section: Introductionmentioning
confidence: 99%